2016
DOI: 10.1128/mcb.00772-15
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin-Related Transcription Factor A and Yes-Associated Protein Exert Dual Control in G Protein-Coupled Receptor- and RhoA-Mediated Transcriptional Regulation and Cell Proliferation

Abstract: The ability of a subset of G-protein coupled receptors (GPCRs) to activate RhoA endows them with unique growth regulatory properties. Two transcriptional pathways are activated through GPCRs and RhoA, one utilizing SRF and its transcriptional co-activator MRTF-A, the other, TEAD and its transcriptional co-activator YAP. These pathways have not been compared for their relative importance and potential interactions in RhoA target gene expression. GPCRs for thrombin and S1P on human glioblastoma cells robustly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 42 publications
5
87
0
Order By: Relevance
“…Recent studies have demonstrated physical interaction between MRTF and YAP independent of their DNA-binding cofactor proteins, SRF and TEAD (Speight et al 2016;Yu et al 2016;Kim et al 2017). The ChIP data presented above and the fact that YAP-TEAD and MRTF-SRF ChIPseq data exhibit only partial overlap suggest that YAP-MRTF interaction is not sufficient to explain the mutual dependence of the two systems.…”
Section: Mrtf and Yap Contribute Independently To Target Gene Regulatmentioning
confidence: 49%
See 2 more Smart Citations
“…Recent studies have demonstrated physical interaction between MRTF and YAP independent of their DNA-binding cofactor proteins, SRF and TEAD (Speight et al 2016;Yu et al 2016;Kim et al 2017). The ChIP data presented above and the fact that YAP-TEAD and MRTF-SRF ChIPseq data exhibit only partial overlap suggest that YAP-MRTF interaction is not sufficient to explain the mutual dependence of the two systems.…”
Section: Mrtf and Yap Contribute Independently To Target Gene Regulatmentioning
confidence: 49%
“…Recent experiments have demonstrated direct physical interactions between the YAP/TAZ WW domain and a conserved PPxY motif at the C terminus of myocardin family proteins, including the MRTFs (Speight et al 2016;Yu et al 2016;Kim et al 2017). Our experiments with constitutively activated MRTF and YAP suggest that these interactions do not directly contribute to the transactivating functions of MRTF.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…26 Yap also interacts with myocardin-related transcription factor A (MRTA), a transcription cofactor, in response to sphingosine-1-phosphate, thereby positively regulating transcription of CYR61 through cooperative actions between the Yap-TEAD pathway and the MRTA-serum response factor pathway. 27 ubiquitin proteasome system. 14 When the Hippo pathway is inactivated, Yap translocates to the nucleus and interacts with multiple transcription factors, including the TEAD/TEF family transcription factors.…”
Section: Ikeda S Et Almentioning
confidence: 99%
“…Lacking the ability to bind directly to DNA, nuclear YAP/TAZ associate with numerous transcription factors to modulate gene expression. Partners of YAP/TAZ include MRTF-A[23], FoxO1[24], Tbx5[25, 26], Runx[27, 28], p73[29], Smads[30, 31], and TEADs among others[32]. YAP/TAZ have been shown to regulate expression of genes that promote cell proliferation, survival and metabolic function.…”
Section: Yap/taz Nuclear Signalingmentioning
confidence: 99%